Scoping review on available delivery systems of short interfering RNA (SiRNA) therapy to treat cardiovascular damage during Covid-19: a study on human and animal models - Yusriha, Nurul Syafika; Rahmat Sam, Mohd Fuad (IIUM Press, International Islamic University Malaysia, 2023)
Background: Short-interfering RNA (siRNA) has the potential to treat a variety of diseases by silencing specific genes. It is currently being considered as an alternative method to treat cardiovascular damage that developed after the Covid-19 infection. If the damage persists for an extended period of time, it will lead to several other cardiovascular problems such as myocarditis. Application of compatible delivery systems can overcome the immunogenicity caused by the off-target reactions and sensitive interaction of siRNA with other cells. Therefore, the purpose of this scoping review was to identify effective delivery systems of siRNA therapy for treating arising cardiovascular problems during Covid-19 based on current studies. Methods: The search applied appropriate keywords involving three online databases: PubMed, Scopus, and ScienceDirect. The article selection was based on Preferred Reporting Items for Systematic Review and Meta-Analyses (PRISMA) guideline and all articles published between 2010 and 2022 that met the inclusion and exclusion criteria were considered. Results: A total of six articles were discovered. Only one study used human cells, while the other five studies used animal models to investigate the effectiveness of distinct types of siRNA in silencing gene expression related to specific cardiovascular damage, which are ischemia-reperfusion injury, myocarditis, myofibroblast, venous thrombosis, and atherosclerosis. The methods of siRNA delivery involved the application of naked siRNA, specific-targeting nanocomplexes, and extracellular vesicles, which were administered through chemical transfection, intravenous injection, and subcutaneous injection. Conclusion: Both in vivo and in vitro approaches have their respective compatible delivery methods and administration routes for each type of siRNA.